Occurrence and Human-Health Impacts of Mycotoxins in Somalia - Wielogorska, Ewa; Mooney, Mark; Eskola, Mari; Ezekiel, Chibundu N; Stranska, Milena; Krska, Rudolf; Elliott, Chris (Journal of agricultural and food chemistry, 2019)
Mycotoxins are secondary metabolites produced by various molds that contaminate many staple foods and cause a broad range of detrimental health effects in animals and humans through chronic exposure or acute toxicity. As such, the worldwide contamination of food and feed with mycotoxins is a significant problem, especially in sub-Saharan Africa. In this study, mycotoxin occurrence in staple foods consumed in Somalia was determined. A total of 140 samples (42 maize, 40 sorghum, and 58 wheat) were collected from a number of markets in Mogadishu, Somalia, and analyzed by a UPLC-MS/MS multimycotoxin method that could detect 77 toxins. All of the maize samples tested contained eight or more mycotoxins, with aflatoxin B1 (AFB1) and fumonisin B1 (FB1) levels reaching up to 908 and 17 322 μg/kg, respectively, greatly exceeding the European Union limits and guidance values. The average probable daily intake of fumonisins (FB1 and FB2) was 16.70 μg per kilogram of body weight (kg bw) per day, representing 835% of the recommended provisional maximum tolerable daily intake value of 2 μg/(kg bw)/day. A risk characterization revealed a mean national margin of exposure of 0.62 for AFB1 with an associated risk of developing primary liver cancer estimated at 75 cancers per year per 100 000 people for white-maize consumption alone. The results clearly indicate that aflatoxin and fumonisin exposure is a major public-health concern and that risk-management actions require prioritization in Somalia.
Keywords: Risk Factors; Somalia; aflatoxin B1; Triticum; Humans; mykotoxiny; Liver Neoplasms; lidé; Aflatoxin B1; Mycotoxins; maximální přípustná koncentrace; Sorghum; kontaminace potravin; Somálsko; Zea mays; Maximum Allowable Concentration; fumonisiny; kukuřice setá; pšenice; nádory jater; Fumonisins; Food Contamination; rizikové faktory